Ultrasmall gold cluster arrays encapsulated in silica nanospheres: applications in fluorescence imaging and catalysis - Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Facile synthesis of ultrasmall gold nanoclusters of size <2 nm dispersible in water using a novel quaternary ammonium ligand is reported. Further, arrays of these nanoclusters are encapsulated in monodisperse silica nanospheres of size 25-30 nm. The photophysical characteristics of the clusters are found to be intact upon encapsulation, rendering the resulting composite material ideal for fluorescence imaging applications. We have further shown the utilization of these materials in catalysis as precursors for Au nanopartides encapsulated in porous silica.

Ultra small nanoclusters to nanoparticles: fine tuning of particle size in water dispersible cation functionalized thiolate protected Pd system - Dhanraj, Prakriti; Samanta, Anupam; Devi, R. Nandini (Materials Today-Proceedings, 2017)
Monolayer protected noble metal nanoparticles have attracted considerable attention in the past decade with potential applications in fields ranging from catalysis to biosensors [1, 2,]. We have developed a novel procedure for the synthesis of water dispersible Pd nanoparticles based on a bifunctional ligand, N,N,N-tripropyl(11-mercaptoundecyl) ammonium chloride in which thiol group binds to the metal, hydrophobic middle alkyl chain acts as capping agent and provides steric stability and on the other end the ammonia group helps in making nanoparticles hydrophilic. In this paper, we report the fine-tuning of size of water dispersible Pd nanosystems ranging from clusters to nanoparticles by adjusting the synthetic parameters and their characterization. (C) 2017 Elsevier Ltd. All rights reserved.